Przekształcenia własnościowe a efektywność - analiza strukturalna na przykładzie przemysłu przetwórczego - Wypych, Mirosław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Over the past several years, fundamental structural changes have been observed in the Polish economy. These changes have been accompanied by possessional transformations and privatization connected with those transformations. Efficiency increment is the main reason for performing privatization processes. This paper is an attempt to verify the above mentioned thesis on the example of manufacturing. The analysis includes the 1995-2004 period and it is based on the Central Statistical Office's data. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 682-689